Fado Resounding : Affective Politics and Urban Life - Gray, Lila Ellen, 1966- (Book collections on Project MUSE., 2013)
This ethnography of fado, Portugal's most celebrated popular music genre, shows how a musical genre can sediment, circulate, and transform affect, sonorously rendering history and place as soulful and feeling as public.